Purification and characterization of a potent dendritic cell activator released by T cells - Lin, Min (2012)
CD8+ T lymphocytes, during priming, can induce robust maturation of dendritic cells (DCs) in a CD40 independent manner by secreting licensing factor(s). I have isolated this so far elusive licensing factor and identified it as GM-CSF. Signaling through the GM-CSF receptor in ex-vivo purified DCs upregulates the expression of costimulatory molecules and provides a positive feedback loop in stimulation of CD8+ T cell proliferation. Combined with a variety of microbial stimuli, GM-CSF supports the formation of potent ‘effector’ DCs capable in screening a variety of proinflammatory cytokines guiding the differentiation of T cells during the immune responses. I have extended this principle to a strong synergism in particular between the Dectin-1 agonist, β-glucan curdlan, and GM-CSF. Both together act in synergy in inducing a strong inflammatory signature which converts immature DCs to potent effector DCs. The synergistic effects of both stimuli resulted in strong IκBα phosphorylation, in its rapid degradation and in enhanced nuclear translocation of all NF-κB subunits. We further identified MAPK ERK as one possible integration site of both signals, since its phosphorylation was clearly augmented when curdlan was co-applied with GM-CSF. Our data demonstrate that the immunomodulatory activity of curdlan requires an additional inflammatory signal provided by GM-CSF to successfully initiate a robust β-glucan specific cytokine and chemokine response. The integration of both signals clearly prime and tailor a more effective innate and adaptive response against invading microbes and fungi.